Metode Bercerita Untuk Mengembangkan Kemampuan Berbicara Anak - Rizky Aulia; Normaliza Normaliza (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This research aims to explore the effectiveness of the storytelling method in developing children's speaking abilities. In the context of early childhood education, speaking ability is a fundamental skill that supports cognitive, social and emotional development. The storytelling method was chosen because it was considered capable of creating a fun and interactive learning atmosphere. This study uses a qualitative approach with a classroom action research design. The research participants involved early childhood children in a kindergarten in Indonesia. Data was collected through observation, interviews and documentation, then analyzed using descriptive analysis techniques. The results of the research show that the storytelling method significantly improves children's speaking abilities, as seen from the increase in vocabulary, sentence structure, and children's courage in speaking in public. Apart from that, this method also increases children's interest and motivation in learning. The implications of this research show that the storytelling method can be used as an effective strategy in teaching language to young children.